Soviet Law Enforcement Agencies (Hrk, Revolutionary Tribunal, Special Department, ChK, GPU, OGPU "Troika", "Five") - S. A., Xoshimov (European Journal of Life Safety and Stability (2660-9630), 2021)
The article is devoted to the activities of the Military Revolutionary Committees, the Revolutionary Tribunal, the Special Forces, the CC, the GPU, the OGPU, the law enforcement agencies established by the Bolsheviks in Turkestan in the process of establishing and consolidating their power.